Parliamentary party loyalty and party family: The missing link?. (March 2018) - Close, Caroline
Party cohesion is a crucial aspect of parliamentary systems, and it varies across time, parties and systems. To explain these variations, scholars have set forth the influence of macro-level and individual-level factors. Although party-level factors have also been considered, the role of party family has been overlooked. This research seeks to fill this gap. To this end, I focus on one dimension of cohesion: the extent to which legislators have internalized the norm of party loyalty. The concept of party family permits to investigate the effect of party origin and party ideology beyond a policy-based approach and left-right dimension. Using attitudinal data of 829 parliamentarians elected in 14 European national assemblies, the analysis uncovers a party family effect, particularly in the green and radical right parties. The results suggest that a greater attention should be directed towards party family as a determinant factor of legislative cohesion.